Emulsifying property, antioxidant activity, and bitterness of soybean protein isolate hydrolysate obtained by Corolase PP under high hydrostatic pressure - Haining Guan; Chunmei Feng; Min Ren; Xiaojun Xu; Dengyong Liu; Xiaoqin Diao (Food Science and Human Wellness)
Enzymatic hydrolysis of proteins can enhance their emulsifying properties and antioxidant activities. However, the problem related to the hydrolysis of proteins was the generation of the bitter taste. Recently, high hydrostatic pressure (HHP) treatment has attracted much interest and has been used in several studies on protein modif ication. Hence, the study aimed to investigate the effects of enzymatic hydrolysis by Corolase PP under different pressure treatments (0.1, 100, 200, and 300 MPa for 1–5 h at 50 ℃) on the emulsifying property, antioxidant activity, and bitterness of soybean protein isolate hydrolysate (SPIH). As observed, the hydrolysate obtained at 200 MPa for 4 h had the highest emulsifying activity index (47.49 m2/g) and emulsifying stability index (92.98%), and it had higher antioxidant activities (44.77% DPPH free radical scavenging activity, 31.12% superoxide anion radical scavenging activity, and 61.50% copper ion chelating activity). At the same time, the enhancement of emulsion stability was related to the increase of zeta potential and the decrease of mean particle size. In addition, the hydrolysate obtained at 200 MPa for 4 h had a lower bitterness value and showed better palatability. This study has a broad application prospect in developing food ingredients and healthy foods.